Penyuluhan Osteoporosis dalam Upaya Pencegahan Komplikasi Tulang pada Pasien Talasemia Mayor di Kabupaten Rembang dan Grobogan - Widyastiti, Nyoman Suci; Retnoningrum, Dwi; Ariosta, Ariosta; Nency, Yetty Movieta; Ngestiningsih, Dwi; Partiwi, Rina; Muniroh, Muflihatul; Naviati, Elsa; Afriana, Rizky Dyas (Journal of Dedicators Community, 2023)
Background Osteoporosis is a complication that often occurs in thalassemia major patients. This complication is still not widely known. This community service program aims to increase the knowledge of families of major thalassemia patients in Rembang Regency and Grobogan Regency regarding the complications of osteoporosis in thalassemia patients. Methods Education about osteoporosis, risk of osteoporosis in thalassemia patients, and prevention of osteoporosis. Extension method with presentation and discussion. The activity was attended by 20 thalassemia families in the Rembang Regency and 21 families of thalassemia patients in the Grobogan Regency. Before and after counseling, pretest and posttest questionnaires were completed to measure the knowledge of families of thalassemia major patients regarding bone complications in thalassemia patients. Results and Discussion Nearly half (46.34%) of respondents did not know the risk of osteoporosis in thalassemia. After counseling, 82.93% of respondents knew the risk of osteoporosis in thalassemia, but there were still 17.07% of respondents who still did not know this risk. Conclusion There is a significant increase in family knowledge of thalassemia major patients about the risk of osteoporosis in thalassemia. Further efforts to increase knowledge are needed with written information media (leaflets) given to families of thalassemia major patients